Risiko operasional dalam perbankan syariah: Tantangan dan strategi pengendalian - faricha, risalatul (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze operational risk in Islamic banking and examine its challenges and control strategies. Operational risk is one of the main risks faced by Islamic banks, arising from internal process failures, human errors, system weaknesses, and external factors. It has greater complexity compared to conventional banking due to the requirement to comply with Sharia principles. This research employs a qualitative approach using literature review from various national and international journals, including publications from the Maliki Interdisciplinary Journal (MIJ). The results indicate that the main challenges in managing operational risk include limited human resource quality, suboptimal implementation of Good Corporate Governance (GCG), and increased risks due to digital transformation, such as cybersecurity threats and system disruptions. Poorly managed operational risk can lead to increased operational costs, reduced efficiency, and decreased customer trust. Therefore, comprehensive control strategies are required, including strengthening internal control systems, improving human resource competencies, implementing consistent GCG practices, and utilizing secure and Sharia-compliant information technology. This study is expected to contribute to the development of more effective operational risk management in Islamic banking.